Enhancing Awareness and Understanding of Halal Products among Micro, Small, and Medium-Sized Enterprises (MSMEs) in Palu City - Nadia, Nadia; Desy Kristiane; Nurinayah Nurinayah; Riskiyani Kaida A Abdullah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2023)
Micro, Small, and Medium Enterprises (MSMEs) often serve as the mainstay of the local economy. However, MSMEs face various challenges in producing and marketing halal products. Despite various strategies being employed to address these issues, the level of awareness and initial understanding among MSMEs regarding halal products and halal certification remains significantly low. Therefore, the objective of this activity is to enhance the awareness and understanding of MSMEs concerning halal products. The activity adopts a participatory approach, involving 39 MSME entrepreneurs as participants. The activity took place at the BTN CPI 3 Hall on Dayodara Street, Talise Valangguni Village, Palu City. The activity process involved several stages, including situational analysis, preparation, focus group discussions, implementation, and evaluation. The results of this activity illustrate that out of the 39 participants involved, 35 of them successfully grasped the importance of halal products and the halal certification registration procedures after receiving the education and awareness-raising provided. This serves as concrete evidence that the program has been successful in increasing the awareness and understanding of MSMEs regarding halal products and halal certification.